2019
DOI: 10.1787/2aac6d21-en
|View full text |Cite
|
Sign up to set email alerts
|

Intra-EEA Stri Database

Abstract: This paper is published under the responsibility of the Secretary-General of the OECD. The opinions expressed and the arguments employed herein do not necessarily reflect the official views of OECD countries. The publication of this paper has been authorised by Ken Ash, Director of the Trade and Agriculture Directorate. This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…Fontagné, Mitaritonna and Signoret (2016 [13]) also find that maximum AVE levels are higher for financial services than for communications, insurance, other business services, and transport. 33 Adopting a methodology closely related to the one chosen for this paper, Benz (2017 [18]) similarly finds the highest AVE levels with respect to financial services, the maximum reported for that sector (1246%) is relatively close to the maximum estimated in this study (1073%). In addition, the range of AVEs provided by Benz (2017 [18]) for communications (between 51% and 299%) is also similar to the non-preferential AVEs for this sector listed in Table 10.…”
Section: Elasticities Of Substitutionsupporting
confidence: 56%
See 3 more Smart Citations
“…Fontagné, Mitaritonna and Signoret (2016 [13]) also find that maximum AVE levels are higher for financial services than for communications, insurance, other business services, and transport. 33 Adopting a methodology closely related to the one chosen for this paper, Benz (2017 [18]) similarly finds the highest AVE levels with respect to financial services, the maximum reported for that sector (1246%) is relatively close to the maximum estimated in this study (1073%). In addition, the range of AVEs provided by Benz (2017 [18]) for communications (between 51% and 299%) is also similar to the non-preferential AVEs for this sector listed in Table 10.…”
Section: Elasticities Of Substitutionsupporting
confidence: 56%
“…Similar to earlier studies that drew upon data observed at one specific point in time (e.g. Benz (2017 [18])), the main analysis therefore relies on cross-sectional variation. Compared to previous studies based on a cross-sectional analysis, collapsing the data across the years 2014-2018 reduces the likelihood that our estimates are influenced by mismeasurement or fluctuations affecting observations in a given year.…”
Section: Estimation Strategymentioning
confidence: 94%
See 2 more Smart Citations
“…The only exception is the European Economic Area (EEA). Services liberalisation within the Single Market of the EEA is measured in the intra-EEA STRI (Benz and Gonzales, 2019).…”
mentioning
confidence: 99%